2013
DOI: 10.1371/journal.pone.0076090
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Peroxide and Nitric Oxide in the Induction of Plant-Encoded RNA-Dependent RNA Polymerase 1 in the Basal Defense against Tobacco Mosaic Virus

Abstract: Plant RNA-dependent RNA Polymerase 1 (RDR1) is an important element of the RNA silencing pathway in the plant defense against viruses. RDR1 expression can be elicited by viral infection and salicylic acid (SA), but the mechanisms of signaling during this process remains undefined. The involvement of hydrogen peroxide (H2O2) and nitric oxide (NO) in RDR1 induction in the compatible interactions between Tobacco mosaic tobamovirus (TMV) and Nicotiana tabacum, Nicotiana benthamiana, and Arabidopsis thaliana was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
4
28
0
1
Order By: Relevance
“…2), as well as the upregulation of SlRDR1 expression at 1 dpi (Fig. 2), results that are supported by previous studies reporting the TMV-induced induction of AOX1a in tomato (Fu et al 2010) andof RDR1 in N. tabacum, N. benthamiana andArabidopsis (Xie et al 2001;Yu et al 2003;Liao et al 2013). These results imply a possible connection between TMV-induced RDR1 upregulation and AOX pathway induction.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…2), as well as the upregulation of SlRDR1 expression at 1 dpi (Fig. 2), results that are supported by previous studies reporting the TMV-induced induction of AOX1a in tomato (Fu et al 2010) andof RDR1 in N. tabacum, N. benthamiana andArabidopsis (Xie et al 2001;Yu et al 2003;Liao et al 2013). These results imply a possible connection between TMV-induced RDR1 upregulation and AOX pathway induction.…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that AOX and antioxidant systems limit H 2 O 2 formation after TMV attack in tomato (Liao et al 2012). In the present study, the silencing of SlAOX1a may have resulted in increased antioxidant systems as a compensation for lower AOX activity after TMV challenge, restricting the accumulation of H 2 O 2 , which might decrease the TMV-induced SlRDR1 transcript level (Liao et al 2013). Therefore, our results suggest that SlAOX1a may be involved in the induction of SlRDR1 in response to TMV infection.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…36,[50][51][52] Briefly, citrus leaf discs were collected from either the Las-infected citrus trees or non-infected trees Figure 1. Las-infected and non-infected sample leaves used in the study.…”
Section: Citrus Leaves and Las Titermentioning
confidence: 99%
“…Interestingly; we observed that the expression of RDR1 was downregulated in mutant plants carrying a 17 amino acid deletion within the DELLA domain of GAI which are insensitive to GA treatment. Given that SA-induced RDR1 expression is dependent on NPR1 protein and is enhanced by H 2 O 2 (Hunter et al, 2013;Liao et al, 2013), it was proposed that DELLA could be attenuating RDR1 expression by its impact on SA signalling and ROS pathways (Rodriguez et al, 2014). Moreover, when viral accumulation was analysed in plants carrying a quadruple DELLA mutation, a reduced viral accumulation was observed in the quadruple DELLA mutants with respect to wild-type plants.…”
Section: Effects Of Tmv Coat Proteinmentioning
confidence: 99%